2016
DOI: 10.5455/medarh.2016.70.437-440
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Marker and Pregnancy Induced Hypertension

Abstract: Background:Pregnancy induced hypertension (PIH) is a state of extremely increased oxidative stress. Hence, research and test of role and significance of oxidative stress in hypertensive disturbance in pregnancy is very important.Aim:Aims of this research were to determine a level of thiobarbituric acid reactive substance (TBARS) as oxidative stress marker in blood of pregnant woman with pregnancy induced hypertension and to analyze correlation of TBARS values with blood pressure values in pregnancy induced hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 16 publications
2
22
0
Order By: Relevance
“…Oxidative stress plays a critical role in the pathophysiology of PE [ 49 ]. The data reveal an increase in oxidative stress in patients with PE, as well as in animal models of PE [ 50 51 52 53 54 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress plays a critical role in the pathophysiology of PE [ 49 ]. The data reveal an increase in oxidative stress in patients with PE, as well as in animal models of PE [ 50 51 52 53 54 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…The elevated level of OS markers such as MDA and 8hydroxy-2 ′ -deoxyguanosine (8-OHdG) and the decreased level of total antioxidant capacity were described by several 4 Oxidative Medicine and Cellular Longevity researchers [11,15,20,37]. Data on the pregnancy-induced hypertension is rare [21][22][23][24], but it also suggests the occurrence of OS. It should be highlighted that the comparison of OS between two groups of patients is challenging.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that preeclampsia is associated with high levels of malondialdehyde (MDA), xanthine oxidase, and glutathione peroxidase and decreased levels of total antioxidant capacity and glutathione [6][7][8][9]. However, data on pathologies such as PIH [21][22][23][24] or IUGR [10][11][12] are rare.…”
Section: Introductionmentioning
confidence: 99%
“…A large-scale study found that the probability of maternal death in mothers diagnosed with PIH after pregnancy was significantly higher than that in normal pregnant women [20]. In addition, PIH is often combined with a number of other disease conditions such as pulmonary edema and liver dysfunction, which also increase the risk of pregnancy-related death [21,22]. With incidence of 9 % and mortality of 3.3/100,000, PIH exerts a great burden on medical and social expenditures in China [23].…”
Section: Discussionmentioning
confidence: 99%